Trapped modes and resonance wave transmission in a plate with a system of notches. (6th January 2018) - Glushkov, E.; Glushkova, N.; Eremin, A.; Lammering, R.
Abstract: The paper deals with guided wave propagation and diffraction in an elastic plate with two and more parallel grooves (notches). It is a continuation of the preceding studies of a single-notch diffraction focused on the manifestation of the trapped mode and resonance transmission effects in the case of several obstacles. Those effects occur at the frequencies close to the nearly real scattering resonance poles, and the forms of wave localization near the notches are predetermined by the eigenforms associated with these poles. Therefore, the change of location of nearly real poles with additional notches and its dependence on their spacing are the issues of prime concern. The increase in number and assembling in groups of resonance poles and transmission peaks, which was known for multi-obstacle guides of other nature, have also been revealed and experimentally confirmed. The theoretical research is conducted on the basis of low-cost semi-analytical models, and the numerical simulation is experimentally validated through the laser Doppler vibrometry. Highlights: Two kinds of resonance transmission (notch-driven and bridge-driven). Multiplication of scattering resonance poles and transmission peaks. Trapped mode manifestation in the transient wave field. Low-cost prediction and experimental confirmation of the effects revealed.